Implementation of Kaulinan Barudak in Forming the Character of Catur Silih: Silih Asah, Silih Asih, and Silih Asuh in Early Childhood - Nurafifah, Lutfia (Jurusan Pendidikan Islam Anak Usia Dini UIN Sunan Gunung Djati Bandung, 2024)
This study aims to analyze the role of Kaulinan Barudak in preserving the values of Catur Silih in Sundanese culture in the modern era. This research uses a descriptive qualitative method with a library research approach. Data were collected from books, journal articles, previous studies, and online publications related to Sundanese culture, traditional games, and Catur Silih values. The results show that Kaulinan Barudak contains cultural values of silih asih, silih asah, silih asuh, and silih wawangi, which contribute to children’s social harmony, character development, and sense of responsibility. However, the preservation of Kaulinan Barudak faces challenges in the digital era due to the dominance of electronic games and limited play space. Integrating traditional games into early childhood education through a culture-based curriculum and technological adaptation can ensure their sustainability. The preservation effort requires collaboration among schools, parents, and the government so that traditional games can be reintroduced to the younger generation in a relevant and meaningful way.